Factors associated with duration of mechanical ventilation at Intensive Care Unit Dr. Soebandi: a retrospective study - Setioputro, Baskoro; Dimas Sumarlan, Rahmawati; Adi Yunanto, Rismawan (Jurnal Ners, 2022)
Introduction: Several factors cause the increase in the duration of mechanical ventilation. This study aims to analyze the relationship between initiating diagnostic factors, age, gender, comorbidities, and mechanical ventilation complications with the duration of mechanical ventilation in the Intensive Care Unit Dr. Soebandi Jember. Methods: This study used a quantitative correlative design with a retrospective approach from medical records. This study used purposive sampling to select samples from 414 total populations, obtaining 81 medical records that met the inclusion criteria. The duration of mechanical ventilation is the dependent variable, while the initiation diagnosis, age, gender, comorbidity, and complications are independent variables. Data were collected using a checklist compiled by the researcher. Data were analyzed using Chi-square and logistic regression. Results: The results showed that there was a relationship between initiation diagnosis (p=0.000) and complication factors (p=0.000) with the duration of mechanical ventilation, while age (p=0.449), gender (p=0.632), and comorbidities (p=0.752) had no relationship with the duration of mechanical ventilation. Multivariate analysis showed that the initiation diagnosis factor was the most dominant factor associated with the duration of mechanical ventilation, with an odds ratio of 11.9 and statistically significant (p=0.000). Conclusions: This study shows that the duration of mechanical ventilation is most dominantly associated with thediagnosis of ventilator initiation and ventilator complications.